Morphology and properties of hollow fiber membrane prepared under different air gap lengths - AIDA ISMA MOHAMAD IDRIS; Syeda Hina Iqbal; Rozita Omar; Hazmin Mansor (Yanbu Journal of Engineering and Science)
The fabrication of hollow fibre membrane modules is affected by many spinning variables, including polymer composition, bath temperature, bore fluid ratio, fibre take-up velocity, and air gap length, resulting in varying properties. This study uses a dry-jet wet-spinning process to investigate the morphology and characteristics of PVDF hollow fibre membranes prepared at 10 cm (P10) and 20 cm (P20) air gap lengths. Polypropylene glycol was used as an additive. The dope extrusion rate, coagulation bath temperature, bore fluid ratio, and take-up velocity were set at 4 rpm, 30°C, 1.5 ml/hr, and 2 m/min, respectively. Atomic force microscopy determined the pore size distribution, roughness, and membrane thickness. Field emission scanning electron microscope (FESEM) analyzed membrane morphology. Membrane performance was tested using 10 mg/L of synthetic protein solution. The results showed that the diameters of the fibers as well as the inner and outer lumens were significantly influenced by the air gap. Membrane dimensions decreased with the increased air gap distance with the outer and inner diameter by 5% at a 10 cm air gap. FESEM images verified that the thickness of the skin layer increases with the increase in air gap distance. The resulting roughness of the membrane layer was found to be dependent on the pore size of the support layer. The protein separation test achieved the best rejection of 98 % using the P20 membrane. Thus, selecting an optimum air gap distance for hollow fibre membrane fabrication was discovered to be a viable strategy for improving separation performance in membrane filtration and improving solute separation in wastewater.